(untitled) - Daniel W Bjork (New York, 1993)
The book is a riveting portrait of a controversial "social inventor" and entrepreneur whose ideas transformed education, child rearing, and even community life. The book explores how the conflict between Skinner's turn-of-the-century small-town upbringing and his avant-garde, intellectual education shaped his science and his ideas about its application
Keywords: b. f. skinner,behaviorism ( psychology ) - united states - history,psychologists - united states - biography